What is the scale factor​
what is the scale factor​ - 1

Answers

Answer 1
Answer:

Answer:

Scale Factor is 7.

Step-by-step explanation:

Each value from the model collum is being multiplied by 7 to get the actual bridge length.

Hope this helped.


Related Questions

Share $420 in the ratio 2:1:4​
What’s the answer to this
What percent of 8 is 4
If alexis ate 2/3 of 1/2 of a pie how much did he eat
What are the possible rational zeros of f(x) = x4 + 6x3 – 3x2 + 17x – 15?.

Is this triangle
ASA
SSS
HL
AAS
SAS
or Not Congruent

Answers

Step-by-step explanation:

With the GIVEN information ( without having to deduce any more information about the triangles)

SAS   says the triangles are congruent   .....  two equal sides with an equal included angle between the sides

Answer:

SAS

Step-by-step explanation:

Angle ABC = Angle ECD

AC = DC

BC = CE

Statement and reasons m<1 +m<2+ m<3=180 whats the reason?

Answers

The correct answer for the question that is being presented above is this one: "the angles of a triangle sum to 180." m<1 +m<2+ m<3=180. The sum of all the angles of a triangle is 180. Since there are 3 angles that form part of a triangle, then the equation m<1 +m<2+ m<3=180  is how it represented it.

3x + y = 17
4x - y = 18

Answers

The two equations given are
3x + y = 17 and 4x - y = 18
Now we will first take one equation
3x + y = 17
Then
y = 17 - 3x
Now replacing the value of y in the second equation we get
4x - y = 18
4x - (17 - 3x) = 18
4x + 3x - 17 = 18
7x = 35
 x = 35/7
   = 5
Putting the value of x in the first equation we get
3x + y = 17
(3 * 5) + y = 17
15 + y = 17
y = 17 - 15
y = 2
So the value of x is 5 and y is 2
3x+y=17
subtract 3x on both sides
y=17-3x
substitute 17-3x for y in the second equation
4x-(17-3x)=18
7x-17=18
7x=35
x=5

and now that you know x=5 you can plug that in to either of the original equations
3(5)+y=17
15+y=17
subtract 15 from both sides
y=2

How can i solve x^3+7x=8x^2

Answers

x^3+7x=8x^2\ \ \ /-8x^2\n\nx^3-8x^2+7x=0\n\nx(x^2-8x+7)=0\iff x=0\ \vee\ x^2-8x+7=0


x^2-8x+7=0\n\na=1;\ b=-8;\ c=7\n\n\Delta=b^2-4ac;\ x_1=(-b-\sqrt\Delta)/(2a);\ x_2=(-b+\sqrt\Delta)/(2a)\n\n\Delta=(-8)^2-4\cdot1\cdot7=64-28=36;\ \sqrt\Delta=√(36)=6\n\nx_1=(8-6)/(2\cdot1)=(2)/(2)=1;\ x_2=(8+6)/(2\cdot1)=(14)/(2)=7\n\n\n\nAnswer:x=0\ or\ x=1\ or\ x=7.
x^3+7x=8x^2\n \nx^3-8x^2+7x =0\n \nx(x^2-8x+7)=0\n \nx=0 \ \ \vee \ \ x^2-8x+7 =0\n \n \Delta = b^(2)-4ac =(-8)^(2)-4*1*7=64 - 28 = 36

x_(1)=(-b-√(\Delta ))/(2a) =(8- √(36))/(2)=(8-6)/(2)= (2)/(2)= 1 \n \nx_(2)=(-b+√(\Delta ))/(2a) =(8+ √(36))/(2)=(8+6)/(2)= (14)/(2)= 7 \n \n Answer : x=0 \ \ \vee \ \ x=1 \ \ \vee \ \ x= 7


Plz factor
2x^2+17x-21

Answers

2x^2 + 17x -21 cannot be factored nicely, if it was +21 you could, but the zeros for this have to gotten using the quadratic equation

-b +/- (b^2-4ac)^1/2
     2a
so

-17 +/- (17^2-4(2)(-21))^1/2
       2(2)
-17 +/- (457)^1/2
       4

so the zeros are roughly 1.094 and -9.594

Yvette is trying to calculate the distance between point C(1, 2) and point D(7, 10). Which of the following expressions will she use? square root of the quantity of 10 minus 2 all squared plus 7 minus 1 all squared square root of the quantity of 10 minus 1 all squared plus 7 minus 2 all squared square root of the quantity of 10 minus 7 all squared plus 2 minus 1 all squared square root of the quantity of 7 minus 10 all squared plus 1 minus 2 all squared

Answers

So this can be solve using the distance formula: D = sqrt [ (x2 – x1)^2 + (y2 – y1)^2] So the expression she should use is: D = sqrt [ (7 – 1)^2 + (10 – 2)^2] Then the answer would be: D = sqrt [ (6)^2 + (8)^2] D = 10

Answer:

square root of the quantity of 10 minus 2 all squared plus 7 minus 1 all squared

Step-by-step explanation: